Design andsynthesis of novelpeptidomimetics for cancer immunotherapy - (:unkn) unknown (My University, 2020)
Tumor cells benefit from some certainsignals, which are referred to as “immune checkpoints”,to escape immune-mediated destruction. With that in mind, it is believed that the blockade of thesepoints, such as programmed cell death Ligand-1 (PD-L1) and programmed cell death 1 (PD-1), can restorean adaptative immune response against tumoral cells.In this study, we have designed and synthesized some novel peptidomimetics with a 2-aminobenzathiazole scaffold, which targetsthe PD-1/PDL-1 pathway. In the viability assay, it was found that these compounds decreased the proliferation of peripheral blood mononuclear cells in the concentration of 10 uM.Overall,ourresults indicate that these novel compounds are potentialcheckpoint inhibitorsforcancer immunotherapy.